2021
DOI: 10.1111/ger.12601
|View full text |Cite
|
Sign up to set email alerts
|

Compatibility of two types of gummy jelly tests for detecting decreased masticatory function

Abstract: Objective This study aimed to verify the compatibility of masticatory performance tests using different two types of gummy jellies. Background data discussing the present status of the field Compatibility between the glucose concentration measuring method (GC) and 10‐steps visual scoring method (VS), which are masticatory performance tests for diagnosing decreased masticatory function (DMF) in oral hypofunction and the use of different types of gummy jelly, has yet to be confirmed. Materials and methods The pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 21 publications
1
10
0
Order By: Relevance
“…In addition, the evaluation methods of both tests were based on the same measurement principle of the degree to which the test sample was crushed. The previous study which evaluated the compatibility of two tests of masticatory ability using gummy jellies of different sizes and hardness reported that the test results showed a positive correlation, which supports the findings of the present study [ 19 ].…”
Section: Discussionsupporting
confidence: 91%
“…In addition, the evaluation methods of both tests were based on the same measurement principle of the degree to which the test sample was crushed. The previous study which evaluated the compatibility of two tests of masticatory ability using gummy jellies of different sizes and hardness reported that the test results showed a positive correlation, which supports the findings of the present study [ 19 ].…”
Section: Discussionsupporting
confidence: 91%
“…Since masticatory performance was thought to be closely related to masticatory behaviors, in the present study, masticatory performance was evaluated not only by the score method, but also by an imaging method to evaluate the increase in surface area of comminuted gummy jelly in order to give a detailed evaluation. With the evaluation of masticatory performance using a test gummy jelly, the significant relationship between the score method and imaging was previously demonstrated [ 17 , 41 ]. In the present study, no significant correlation was found between increased surface area of the comminuted gummy jelly and number of chews of a rice ball.…”
Section: Discussionmentioning
confidence: 99%
“…FruitSwing Hue-Check mastication can adversely impact both. 6,22 The repercussions of this decline can extend beyond oral health and crucially affect the overall well-being, especially in age-advanced frail older adults. 7,23 Therefore, assessing and monitoring masticatory performance in older adults is quite pertinent.…”
Section: Gummy Jellymentioning
confidence: 99%
“…2 Recently, a shift towards simpler evaluation techniques for the assessing masticatory performance has occurred, and these techniques employ novel test materials including chewing gum, 3,4 paraffin wax, 5 or gummy jelly. 1,2,6,7 The chewing gum methods have been more frequently used in recent times and have gained popularity because of their ease of use, making them less cumbersome and less time-consuming. This method involves chewing either colour-changing chewing gums or two-colour chewing gum for a specified number of chewing cycles (depending on the method).…”
Section: Introductionmentioning
confidence: 99%